Psychosocial Risk Factors on Mining Workers Processing Copper and Gold Minerals during Covid-19 Pandemic - Khaerani Suci Lestari; Aditya Fadilah Muhamad; Edi Karyono Putro; John Charles Wilmot; Yenni Miranda Savira; Aprilia Listiarini; Donny Zulfakar; Stevan Deby Anbiya Muhamad Sunarno; Arif Susanto (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: In the era of the Covid-19 pandemic, psychosocial issues as part of health and safety have become a popular mental health issue, particularly among gold and copper miners. This situation has led some companies to fire their unskilled and unproductive workers to minimize the production costs. However, there is no specific regulation for the workers that could be a barrier of this unpredicted situation. This condition mostly becomes a negative stressor for the workers at the jobsite. At some point, it develops to a critical health and safety condition known as risky and unhealthy behavior that brings to fatality. The aim of this research is to analyze the psychosocial risk factors that adversely affect the psychology of copper and gold mining workers during the pandemic. Method: This is a cross-sectional study with COPSOQ III, used to identify factors contributing to workers’ psychology, while Dolan & Arsenault’s questionnaire was used to analyze stress symptoms, with a Cronbach α value of 0.83-0.84. Results: Multivariate tests were conducted on the variables of work experience, body mass index, marital status, emotional demands, vertical trust, and organizational justice. Significance values were obtained for the variables of work experience (0.590 body mass index (0.517), marital status (0.122), emotional demands (0.187), vertical trust (0.000), and organizational justice (0.119). Of the six variables, only vertical trusthad a significant value. Conclusion: Psychological risk factors on copper and gold mining workers during the pandemic are only influenced by a vertical trust.Keywords: COPSOQ III, leadership, pandemic, psychosocial, vertical trust